HFI/NQI 2004 Proceedings of the 13th International Conference on Hyperfine Interactions and 17th International Symposium on Nuclear Quadrupole Interactions, (HFI/NQI 2004) Bonn, Germany, 22-27 August, 2004 - Maier, K.; Vianden, R. (Springer Berlin Heidelberg : Imprint: Springer, 2005)
Proceedings of the 13th International Conference on Hyperfine Interactions and 17th International Symposium on Nuclear Quadrupole Interactions, HFI/NQI 2004, held in Bonn, Germany, 22-27 August, 2004 Researchers and graduate students interested in the Mössbauer Effect and its applications will find this volume indispensable. The volume presents the most recent developments in the methodology of Mössbauer spectroscopy. Reprinted from Hyperfine Interactions (HYPE) Volume 158/159.